Studies of adsorptive capacity of bacterial β-glucosidases on lignocresol aiming the enzymatic recycling in bioprocesses - Barduco Ferreira, Mariana T. [UNESP]; Zuccari, Thiago B.B. [UNESP]; Garcia, Wanius; de Oliveira Neto, Mario [UNESP] (Elsevier, 2019)
Enzymes are essential in many biological processes, including second-generation ethanol production. However, enzymes are one of the main expenses for the industrial process in these days. Several studies have been done to maximize cost savings, however, many processes are still economically infeasible. In this study, we report the synthesis of a suspension of lignocresol for recycling or reuse of enzymes in bioprocesses. In this way, it was performed the adsorption assays between lignocresol and β-glucosidases from Thermotoga petrophila, belonging to the families GH1 and GH3, for the development of a lignocresol-enzyme complex. Our results show that lignocresol maintains greater adsorptive capacity for β-glucosidases than lignin. This capacity can be explained both by its great hydrophobicity and also by electrostatic characteristics. Therefore, all these results demonstrate good adsorption of the enzymes to the lignocresol, demonstrating great potential for enzymatic recycling.
Keywords: Adsorption; Lignin; Lignocresol; β-Glucosidase